Biblioteki i media w czasie pandemii COVID-19 Bibliografia selektywna - Kowalska, Marzena (Acta Universitatis Lodziensis. Folia Librorum, 2021)
Selective bibliography of monographies and articles from representative scientific and professional journals in the field of information science and book science as well as social communication and media, which were published in Poland in 2020 and 2021 (until August 2021).